Impaired gamma-band activity during perceptual organization in adults with autism spectrum disorders: Evidence for dysfunctional network activity in frontal-posterior cortices - Sun, L.; Grützner, C.; Bölte, Sven; Wibral, M.; Tozman, T.; Schlitt, S.; Poustka, F.; Singer, W.; Freitag, C.; Uhlhaas, P. (Society for Neuroscience, 2012)
Current theories of the pathophysiology of autism spectrum disorders (ASD) have focused on abnormal temporal coordination of neural activity in cortical circuits as a core impairment of the disorder. In the current study, we examined the possibility that gamma-band activity may be crucially involved in aberrant brain functioning in ASD. Magneto-encephalographic (MEG) data were recorded from 13 adult human participants with ASD and 16 controls during the presentation of Mooney faces. MEG data were analyzed in the 25-150 Hz frequency range and a beamforming approach was used to identify the sources of spectral power. Participants with ASD showed elevated reaction times and reduced detection rates during the perception of upright Mooney faces, while responses to inverted stimuli were in the normal range. Impaired perceptual organization in the ASD group was accompanied by a reduction in both the amplitude and phase locking of gamma-band activity. A beamforming approach identified distinct networks during perceptual organization in controls and participants with ASD. In controls, perceptual organization of Mooney faces involved increased 60-120 Hz activity in a frontoparietal network, while in the ASD group stronger activation was found in visual regions. These findings highlight the contribution of impaired gamma-band activity toward complex visual processing in ASD, suggesting atypical modulation of high-frequency power in frontoposterior networks.